Graphs, Maps, Trees: Abstract Models for a Literary History - Moretti, Franco 1950- (London Verso, 2005)
In this groundbreaking book, Franco Moretti argues that literature scholars should stop reading books and start counting, graphing, and mapping them instead. In place of the traditionally selective literary canon of a few hundred texts, Moretti offers charts, maps and time lines, developing the idea of “distant reading” into a full-blown experiment in literary historiography, in which the canon disappears into the larger literary system. Charting entire genres—the epistolary, the gothic, and the historical novel—as well as the literary output of countries such as Japan, Italy, Spain, and Nigeria, he shows how literary history looks significantly different from what is commonly supposed and how the concept of aesthetic form can be radically redefined.
Includes bibliographical references and index.
Keywords: Literature; History; Historiography; Esthetics